Solvothermal reduction of graphene oxide for carbon paste electrode and its application in trace lead detection - Kok, Alvin Wei Jie (2014)
Industries’ failure to manage waste responsibly has led to contamination of water resources with heavy metals such as lead (Pb), cadmium and copper into the environment. These heavy metals have gained considerable interest as they can accumulate in the kidney, lung and liver, allowing sub-toxic exposure levels to pile up to toxic levels over time. Hence, fast detection of trace heavy metals in aqueous solution is essential to reduce fatal incidents that were caused by the consumption of polluted water. Hence, the objective of this project was to fabricate an enhanced carbon paste electrode (CPE) for detection of trace Pb.